Veliparib in combination with radiotherapy for the treatment of MGMT unmethylated glioblastoma - Jue, Toni Rose (J Transl Med, 2017)
BACKGROUND: The O (6)-methylguanine methyltransferase (MGMT) gene is frequently unmethylated in patients with glioblastoma (GBM), rendering them non-responsive to the standard treatment regime of surgery followed by concurrent radiotherapy (RT) and temozolomide. Here, we investigate the efficacy of adding a PARP inhibitor, veliparib, to radiotherapy to treat MGMT unmethylated GBM. METHODS: The inhibition of PARP with veliparib (ABT-888), a potent and orally bioavailable inhibitor in combination with RT was tested on a panel of patient derived cell lines (PDCLs) and patient-derived xenografts (PDX) models generated from GBM patients with MGMT unmethylated tumors. RESULTS: The combination of veliparib and RT inhibited colony formation in the majority of PDCLs tested. The PDCL, RN1 showed significantly reduced levels of the homologous repair protein, Mre11 and a heightened response to PARP inhibition measured by increased apoptosis and decreased colony formation. The oral administration of veliparib (12.5 mg/kg, twice daily for 5 days in a 28-day treatment cycle) in combination with whole brain RT (4 Gy) induced apoptosis (Tunel staining) and decreased cell proliferation (Ki67 staining) in a PDX of MGMT unmethylated GBM. Significantly longer survival times of the PDX treated with the combination treatment were recorded compared to RT only or veliparib only. CONCLUSIONS: Our results demonstrate preclinical efficacy of targeting PARP at multiple levels and provide a new approach for the treatment of MGMT unmethylated GBM.